Migration, memory, and diversity : Germany from 1945 to the present - Wilhelm, Cornelia, 1964- (Berghahn Books, 2017)
"Within Germany, policies and cultural attitudes toward migrants have been profoundly shaped by the difficult legacies of the Second World War and its aftermath. This wide-ranging volume explores the complex history of migration and diversity in Germany from 1945 to today, showing how conceptions of 'otherness' developed while memories of the Nazi era were still fresh, and identifying the continuities and transformations they exhibited through the Cold War and reunification. It provides invaluable context for understanding contemporary Germany's unique role within regional politics at a time when an unprecedented influx of immigrants and refugees present the European community with a significant challenge"--Publisher description.
Keywords: Germany -- Emigration and immigration -- Social aspects.; Immigrants -- Germany -- Social conditions.; Refugees -- Germany -- Social conditions.; Minorities -- Germany -- Social conditions.; World War, 1939-1945 -- Influence.; Memory -- Social aspects -- Germany.; Cultural pluralism -- Germany.; Multiculturalism -- Germany.; Difference (Psychology) -- Social aspects -- Germany.; Germany -- Ethnic relations.; Allemagne -- Émigration et immigration -- Aspect social.; Minorités -- Allemagne -- Conditions sociales.; Guerre mondiale, 1939-1945 -- Influence.; Diversité culturelle -- Allemagne.; Multiculturalisme -- Allemagne.; Psychologie différentielle -- Aspect social -- Allemagne.; SOCIAL SCIENCE -- Emigration & Immigration.; SOCIAL SCIENCE / Emigration & Immigration; Cultural pluralism; Difference (Psychology) -- Social aspects; Emigration and immigration -- Social aspects; Ethnic relations; Immigrants -- Social conditions; Influence (Literary, artistic, etc.); Memory -- Social aspects; Minorities -- Social conditions; Multiculturalism; Refugees -- Social conditions; Germany; 1939-1945